Comprehensive biomarker analysis from phase II study of nivolumab in patients with thymic carcinoma - Katsuya, Yuki; Kitano, Shigehisa; Yamashita, Makiko; Ouchi, Mayu; Yagishita, Shigehiro; Hamada, Akinobu; Nakamura, Hiromi; Hosoda, Fumie; Shibata, Tatsuhiro; Motoi, Noriko; Nakayama, Takayuki; Seto, Takashi; et al. (Frontiers in Oncology, 2023)
In a phase II trial of nivolumab in advanced thymic carcinoma (UMIN000022007), long SD (SD for more than 24 weeks) was seen in three patients and irAE (Gr2 or higher) was seen in four patients among 15 patients. Here, we report preplanned comprehensive biomarker analyses. We obtained tumor samples for immunohistochemistry, peripheral blood mononuclear cells (PBMCs), plasma and serum for pharmacokinetic analysis of nivolumab and cytokine evaluations, and whole blood for immuno pharmacogenomic (PGx) analysis. PD-L1 expression on tumor cells were not associated with therapeutic efficacy, but FOXP3 expression in tumor area and stroma, CD204 expression in stroma, and MHC class I in tumor area were all low among long SD patients. PBMC of long SD patients presented with larger number of naïve/memory cells prior to treatment, suggesting priming after nivolumab administration. Immuno-PGx analysis showed non-synonymous SNVs in ITGAX and PDCD1 had some correlation with PFS. Concentration of nivolumab in blood during the treatment was not related to PFS, with their overall trend towards decreased nivolumab concentration in patients with irAEs. Low immunogenicity of thymic carcinoma demonstrated in our study may require the activation of immune systems via a combination of immune checkpoint blockades.